Establishing trust between energy aware nodes in MANETs: a family relationship-based approach. (2016) - Ramana, V. Venkata; Reddy, A. Rama Mohan
Mobile ad-hoc networks (MANETs) solely depends on cooperation between neighbour nodes in the network. The characteristics like topology changes, node mobility and node failure distinguish it from traditional networks and make it more vulnerable to attacks. Establishing trust between nodes plays a major role in MANETs as most of the attacks are performed by selfish and malicious nodes inside the network. There were many security schemes proposed based on cryptography, but all rely on centralised trust authority and pre-established infrastructure which is not possible in MANETs. Resource limitation parameters like energy constraint and signal strength will have to be considered in establishing trust. So we have proposed a family relationship routing protocol (FRRP) which assigns different relationship and privileges to nodes in the network based on direct and indirect trust by considering resource limitation parameters. This paper aims at providing decentralised and distributed trust management scheme to MANETs which does not depend on any predefined assumption.